Co-transplantation of Schwann and Bone Marrow Stromal Cells Promotes Locomotor Recovery in the Rat Contusion Model of Spinal Cord Injury - Mohammad Taghi Joghataei; Mehrdad Bakhtiari; Abolfazl Faghihi; Mehdi Mehdizadeh; Bagher Pourheydar; Fereshteh Mehraein; Babak Behnam; Vahid Pirhajati (Cell Journal, 2010)
Objective: Previous studies have shown that transplantation of bone marrow stromalcells (BMSCs) into the contused spinal cord improves functional recovery and that administrationof Schwann cells (SCs) after spinal cord injury (SCI) facilitates axonal regeneration.Although the efficacy of these treatments have been proven, when used individually,their resulting number of regenerated axons is small and locomotor recovery is modest;therefore, we decided to research whether co-transplantation of these cells can improvethe outcome.Materials and Methods: Adult male Wistar rats (n=56), each weighting 250-300 gramswere used. BMSCs and SCs were cultured and prelabeled with BrdU and 1,1' dioctadecyl3,3,3',3' tetramethylindocarbocyanin perchlorate respectively. Contusion model of SCIwas performed at the T8-9 level using NYU device (New York University device). The ratswere divided into seven groups, each consisting of 8 animals. These groups included: acontrol group, three experimental groups and three sham groups. In the control group,only a laminectomy was performed. The three experiment groups were the BMSC, SCand co-transplant groups, and 7 days after injury, they received intraspinal BMSCs, SCsand the combination of BMSCs & SCs respectively. The sham groups received serum inthe same manner. Locomotion in the groups was assessed using the basso, beatie andbresnahan (BBB) test at 1, 7, 14, 21, 28, 35, 42, 49 and 56 days after SCI.Results: More significant improvement was observed in the BBB scores of the co-transplantgroup (p<0.05) in comparison with BMSC and SC groups.Conclusion: This study shows that co-transplantation of BMSCs and SCs may provide apowerful therapy for SCI and become required for the development of combinatory treatmentstrategies in the future.